The demands of a women's college soccer season - Gentles, J. A.; Coniglio, C. L.; Besemer, M. M.; Morgan, J. M.; Mahnken, M. T. (Sports, 2018)
The purpose of this study was to use GPS, accelerometers, and session rating of perceived exertion (sRPE) to examine the demands of a Division II women`s soccer team. Data was collected on 25 collegiate Division II women`s soccer players over an entire regular season (17 matches and 24 practices). ZephyrTM BioHarnesses (BHs) were used to collect tri-axial acceleration information and GPS derived variables for all matches and practices. Acceleration data was used to calculate Impulse Load, a measure of mechanical load that includes only locomotor related accelerations. GPS was used to quantify total distance and distance in six speed zones. Internal Training Loads were assessed via sRPE. Mean Impulse Load, total distance, and sRPE during match play was 20,120 ± 8609 N·s, 5.48 ± 2.35 km, and 892.50 ± 358.50, respectively. Mean Impulse Load, total distance, and sRPE during practice was 12,410 ± 4067 N·s, 2.95 ± 0.95 km, and 143.30 ± 123.50, respectively. Several very large to nearly perfect correlations were found between Impulse Load and total distance (r = 0.95; p < 0.001), Impulse Load and sRPE (r = 0.84; p < 0.001), and total distance and sRPE (r = 0.82; p < 0.001). This study details the mechanical demands of Division II women`s soccer match play. This study also demonstrates that Impulse Load is a good indicator of total distance.